A Good Alternative to Numerical Methods of Integration for the Simulation of Chemical Kinetics: The Monte Carlo Method - Tighezza, A.; Aldhayan, D.; Rezgui, Y.; Alarifi, A. (Asian Journal of Chemistry, 2016)
This paper illustrates the ways in which Monte-Carlo method provides a powerful tool for a simulation of complex reactions. New software using this method is described and tested on complex systems. The most important improvement in this software is the suppression of limitation on number of species and number of steps of the reaction mechanism.